Function of transient receptor potential canonical 3 - Nicotinamide adenine dinucleotide phosphate oxidase 2 interaction in atrophy of cardiac and skeletal muscle cells - Suhaini Sudi (2020)
Muscle atrophy develops after a long period of inactivity caused by malnutrition, ageing, genetic disorders, and cancer. High protein degradation rate is a hallmark in the muscle atrophy-related diseases that showed increase in reactive oxygen species (ROS) production and severe muscle wasting. The signaling pathways involving the activation of protein degradation systems are complex and regulated by many different mediators, therefore finding a specific target is a major challenge for muscle atrophy. In general, the current study aimed to reveal new key components of the protein degradation pathway involved in muscle cells atrophy. The first part of the study was to determine the involvement of transient receptor potential canonical 3 (TRPC3) and NADPH oxidase 2 (Nox2) complex in cardiac atrophy on a primary culture of neonatal rat cardiomyocytes (NRCMs) using immunostaining, western blot and luciferase assay. High concentration of adenosine triphosphate (ATP) significantly induces NRCMs atrophy through ROS-mediated up-regulation of atrophy marker, muscle atrophy F-box (MAFbx) and reduction in cell size (p<0.05). Gene knockdowns of TRPC3 and Nox2 significantly suppressed ATP-induced NRCM atrophy and ROS production (p<0.05). The study further revealed that TRPC3 and Nox2 formed an interaction in the presence of ATP through the P2Y2 receptor in NRCMs atrophy. Furthermore, nutrient depletion (glucose starvation, hypoxia, and amino acid deprivation) displayed a significant increase in extracellular ATP levels that promoted NRCMs shrinkage (p<0.05). The second part of the study designed to provide direct evidence of TRPC3-Nox2 complex formation in in vivo setting incorporating with human disease models of skeletal muscle atrophy using immunohistology and quantitative polymerase chain reaction (qPCR). Denervation surgery was conducted in the hind limb of wild type (WT) and TRPC3 gene knockout (C3KO) mice to evaluate the effect of immobilization-induced skeletal muscle atrophy on TRPC3-Nox2 complex. Expectedly, 14 days post denervation significantly induces muscle atrophy and ROS overproduction in soleus, gastrocnemius, and tibia/is anterior tissue sections. However, the deletion of TRPC3 prevented denervationinduced atrophy only in C3KO soleus. A significant up-regulation of Nox2 protein promotes interaction with TRPC3 protein in denervation-induced soleus atrophy. Finally, transgenic mice carrying a mutant superoxide dismutase 1 gene (SODl) that mimic Amyotrophic Lateral Sclerosis disease displayed a significant decrease in fibre sizes associated with overproduction of ROS in gastrocnemius and tibia/is anterior (p<0.05) but not in soleus (p>0.05). Nevertheless, atrophied fibres from transgenic mice failed to demonstrate a significant increase in Nox2 protein up-regulation, which suggests the SODl-induced atrophy pathway is most likely independent to TRPC3- Nox2 complex-mediated ROS production in soleus atrophy induced by denervation. This study demonstrated the function of TRPC3 and Nox2 complex formation in cardiomyocytes atrophy and skeletal muscle atrophy, specifically in slow oxidative soleus muscle. Furthermore, this study may provide potential therapeutic targets that can delay or counteract muscle atrophy in a specific condition.